2011
DOI: 10.1083/jcb1941oia4
|View full text |Cite
|
Sign up to set email alerts
|

Pten mediates Myc oncogene dependence in a conditional zebrafish model of T cell acute lymphoblastic leukemia

Abstract: The MYC oncogenic transcription factor is overexpressed in most human cases of T cell acute lymphoblastic leukemia (T-ALL), often downstream of mutational NOTCH1 activation. Genetic alterations in the PTEN-PI3K-AKT pathway are also common in T-ALL. We generated a conditional zebrafish model of T-ALL in which 4-hydroxytamoxifen (4HT) treatment induces MYC activation and disease, and withdrawal of 4HT results in T-ALL apoptosis and tumor regression. However, we found that loss-of-function mutations in zebrafish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
1
29
0
1
Order By: Relevance
“…Circular rag2:myr-mAkt2 plasmid DNA (30 pg) was microinjected along with I-SceI meganuclease (New England Biolabs) into one-cell stage zebrafish embryos from the AB wild-type strain, as previously described (26). Immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Circular rag2:myr-mAkt2 plasmid DNA (30 pg) was microinjected along with I-SceI meganuclease (New England Biolabs) into one-cell stage zebrafish embryos from the AB wild-type strain, as previously described (26). Immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…cMYC-ER zebrafish 22 were crossed with lck:EGFP zebrafish and leukemic adults were identified via fluorescence microscopy for T-ALL dissemination. Leukemic adults were treated either with vehicle or LDK on a 2-day-on, 1-day-off treatment regimen with daily water changes.…”
Section: Leukemic Zebrafish Experimentsmentioning
confidence: 99%
“…Using an inducible MYC-dependent zebrafish T-ALL model, Gutierrez et al found that established tumors regressed when MYC expression was turned off. This effect was circumvented by activating PI3K-AKT signaling, 66 showing that AKT activation is an important downstream effector of MYC which may drive GSI resistance. Moreover, the MYC gene is an important…”
mentioning
confidence: 99%